O corpo e a diversidade de gênero no ensino da biologia no contexto da educação pública - Caio César Souza Coelho (2022)
Observing the difficulty of high school teachers in addressing issues of gender diversity and sexuality, and in view of the absence of this subject in books and teaching materials in the areas of biological sciences, the present work intended, through actions that bring the student closer to their reality, to approach and associate hormones, body, society, diversity, and gender, strengthening in school the role of plurality in the lives of all beings. This work presents a didactic sequence divided into two pedagogical interventions: primary introduces and presents the importance of teaching biology for issues of puberty, body changes, youth body and gender awareness. It created, through scientific teaching, questions about body diversity and gender designations. Following, in turn, considers on the teaching of biology from a queer perspective, carrying out a junior scientific initiation project with two students who produced a documentary with transsexual people, animations on gender and body diversity, as well as participation in public debate. The work highlights the importance of education for sexual and gender diversity, as well as fostering the importance of gender discussions with both the human and biological sciences. In this way, the works carried out by the students were evaluated seeking an inclusive perspective for the LGBT+ population, considering the individuality of a way of living. Finally, the work resumes the discussions about the importance of scientific initiation at the high school level and tries to break the view of gender based solely and exclusively on biology.